Implementasi âPresidential Amnesty Programmeâ Tahun 2009-2014 dalam Mencapai Perdamaian di Delta Niger, Nigeria - , INDRA BUWANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Niger Delta is a oil producing Regionof Nigeria. Though blessed with abundant supply of oil, the area plunged into a deep rooted conflict caused by poverty. The stagnation of development haunts the land as armed groups keeps trying to steal the oil. The problems addressed poorly and the conflicts still linger as the consequence. President Umaru Musa Yarâadua launched Presidential Amnesty Programme to addres the conflict in Delta Niger. The programme gives amnesty and a chance for the militants to support their future through vocational training. The programme is trying to achieve peace in Niger Delta, but faces many challenges as it strives to reduce the armed groups attack. This study examines Presidential Amnesty Programme in achieving peace in the Niger Delta Region of Nigeria. Peace which the programme wants to achive is negative peace. Negative peace emphasizes in lowering the amount of collective violence in the conflict. Using the concepts of amnesty, DDR, and peace, negative peace in particular, this paper analyzes whether Presidential Amnesty Programme succeeded in facing the challenges of Niger Delta Conflict and eventually lead to peaceful situation or not. This paper argues that the programme succeeded in reducing the number of active militants in Niger Delta and also has a positive side effect in rising the production of oil because the decline of armed groups attack after the implementation of the programme. Even so, it failed to achieve negative peace in the region because the armed group attack start to rise again not long after the implementation of the programme, though it is not worse than before the implementation of the programme. The Presidential Amnesty Programme is not an elixir to cure all the problems in Niger Delta Region which caused the conflict. The achievements of Presidential Amnesty Programme should be used as a stepping stone for the next program to achieve greater peace. Peace needs to be worked out with full commitment to achieve it by all parties which have interest in Niger Delta or else the duration of conflict will never end.